KUALITAS BAKTERIOLOGIS CABAI GILING YANG DIJUAL DI PASAR TRADISIONAL WILAYAH PONDOK GEDE - Mega Mirawati; Husjain Djajaningrat; Angki Purwanti (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
Milled chili is the result of milling fresh chili, with or without the preservatives. In the manufacture of milled chili, there's so many milled chili processing that use rot chili as the raw materials. it can lead contamination by the bacteria that cause of food poisoning. According to ISO 2011, the maximum limit of microbial contamination in seasoning include milled chili is Salmonella sp negatif/25g, Staphyllococcus aureus 1x102 colonies / g and MPN Coliform 100/g. This research aims to determine the bacteriological quality of milled chili which are sold in the traditional markets at Pondok Gede area and the percentage of milled chili with good quality. This research is experimental research with milled chili samples are sold in traditional markets at Pondok Gede area. this research was done at the Laboratory of Bacteriology Department Analis Kesehatan Poltekkes Kemenkes Jakarta III. the methods were used are culturing and the Most Probable Number (MPN). The result of 32 samples milled chili, was found 11 samples with a good quality because there is not overgrown by the bacteria and 21 samples are not in good quality because were found the bacteria was growing with the amount exceeds the maximum bacteria contamination limits which specified in ISO. The raw materials, water for washing chili, packaging, sanitation, and the use of preservatives affect the quality of milled chili. Conclusion that not all milled chili are sold in traditional markets at Pondok Gede area have good quality and the percentage of milled chili with good quality is 34,375% and not good quality is 65,625%